Voices and challenges of marginalized and vulnerable groups in urban informal settlements in Nairobi, Kenya: building on a spectrum of community-based participatory research approaches - Karuga, Robinson; Kabaria, Caroline; Chumo, Ivy; Okoth, Linet; Njoroge, Inviolata; Otiso, Lilian; Muturi, Nelly; Karki, Jiban; Dean, Laura; Tolhurst, Rachel; Steege, Rosie; Ozano, Kim; et al. (Frontiers in Public Health, 2023)
There is a growing awareness in the literature that sluminformal settlements are heterogeneous and that there is a need to develop the evidence base on how vulnerabilities and inequities are experienced to inform nuanced and context specific action, policy and practice. This paper contributes to this literature by illuminating the value of an overarching Community Based Participatory Research (CBPR) approaches, and partnerships with community co-researchers to jointly develop evidence on inequities and how they are experienced. We demonstrate how social mapping can be used to identify the particularly most vulnerable and marginalized groups, and how vulnerability and marginality are experienced. Governance diaries have a particular value in illuminating actors for accountability and the various people and institutions with the power to influence health and wellbeing; whilst photovoicephoto voice highlighted the lived experiences of vulnerability and marginality. By applying creative participatory methods including social mapping, photovoicephoto voice and governance diaries in partnership with community members; vulnerabilities and marginalization were made visible and lived experiences could be captured and shared to stimulate collaborative action for specific interventions and for demanding accountability on health inequity.